Genetic transformation in the methanogen Methanococcus voltae PS. - Bertani, G (1987)
Mutations causing requirements for histidine, purine, and vitamin B12 were obtained in strain PS of Methanococcus voltae (archaebacteria) upon irradiation with UV or gamma rays. The first two mutations were shown to revert at low frequencies and were used to demonstrate the occurrence of transformation with homologous, wild-type DNA. The transformation rates obtained for these presumably chromosomal markers were in the range of 2 to 100 transformants per microgram of DNA. Mutants resistant to 2-bromoethanesulfonate and to 5-methyl-DL-tryptophan were also isolated.